GAME HAGO BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN: Juridical Analysis of Hago Game Advertisements Based on Consumer Protection Law Number 8 of 1999 - Faqih Adhyaksa Kusuma; Renti Maharaini Kerti (Faculty of Law, Universitas Trisakti, 2024)
Principally, advertisements must comply with laws and regulations in the field of advertising and consumer protection, but there are still many advertisements that violate, for example, Hago advertisements that have violated regulations in the field of advertising because they harass the dignity of teachers and display teachers who are discriminatory against students who use Hago Game, so this study will analyze violations of Hago Game advertisements based on consumer protection. The problem raised is regarding whether Hago advertisements have met the criteria for good advertising in the perspective of consumer protection and analyzing who can be held liable if Hago advertisements are re not good advertisements. This research uses normative type research methods. The result is, Hago's advertisement does not meet the criteria for good advertising because it violates Article 17 section (1) letter f UUPK because it violates the regulations in the advertising sector, namely Article 58 section (4) letter h SPS and Article 16 section (2) letters a and b SPS. The conclusion is ones responsible should be the companies that make advertisements and broadcasting institutions based on professional responsibility